Design, development and evaluation of veterinary transdermal film of Azadirachta indica extract for treatment of mastitis - Prabhu, Shreya A.; Dasankoppa, Fatima S.; Sholapur, Hasanpasha N.; Sagare, Revati D. (Journal of Advanced Veterinary Research, 2024)
Mastitis is an infectious disease condition resulting in inflammatory reaction which occurs when a large number of leukocytes migrate into the mammary gland. Mastitis causes significant financial losses for the global dairy industry. The present study aimed at development of transdermal film comprising of Azadirachta indica extract for treatment of mastitis, which is economical, safe and will not emerge multidrug resistance amongst pathogens. Azadirachta indica extract was prepared by sonication method. The extract was evaluated for minimum inhibitory concentration against gram-positive and gram-negative organisms. Transdermal films with Azadirachta indica extract were prepared with ethylene vinyl acetate and polyvinyl acetate then subjected for the physical characterization, drug content, in vitro dissolution, tensile strength and antibacterial activity. The minimum inhibitory concentration of extract displayed 5mg/ml. Based on quantification of azadirachtin by UV spectrophotometer 100 mg of extract was incorporated in each transdermal film. Transdermal films of Azadirachta indica extract possessed desirable physical properties, and exhibited the drug release of 91.54% in 8 hours. Transdermal film of Azadirachta indica showed sensitivity with a zone of inhibition of 19mm, 16mm, 19mm and 22mm against Staphylococcus aureus, Escherichia coli, Bacillus subtilis and Pseudomonas aeruginosa respectively. Data obtained revealed that transdermal films of Azadirachta indica extract exhibited good drug release profile and desirable physical properties, with good antibacterial activity. The present work reveals that transdermal film of Azadirachta indica extract can be considered for the treatment of mastitis.